The relationship between online impulsive buying behaviour, materialism, and subjective wellbeing among Malaysian young adults - Foong, Kai Jie; Chong, Ka Yee; Lee, Shun Yi (2022)
In this consumer-oriented era, the acquisition of materials is considered to be the new prosperity. Purchasing and acquisition of materials become the current norm that linked to one’s subjective wellbeing (SWB). Many especially young adults use the internet to make impulse purchases until they lost themselves and even went bankrupt while pursuing a high level of life fulfilment and happiness. This sparked a curiosity in seeing if there was a relationship between online impulsive buying, success materialism, happiness materialism, and SWB among Malaysian young adults. Hence, a cross-sectional study was used to conduct the research. A total of 372 young adults aged 18-25 years old from different states of Malaysia were recruited by purposive sampling. Data was collected via distributing the online survey on social networks. In this study, Impulse Buy Scale (IBS; Beatty & Ferrell, 1998), Material Value Scale-Short form (MVS; Richins, 2004) and Satisfaction with Life Scale (SWLS; Diener, 1985) were used to measure the variables. After analysis, the findings reveal a significant negative relationship between happiness materialism and SWB. However, there was no significant correlation between online impulsive buying, success materialism, and SWB. The findings of this study add additional support for the Maslow’s hierarchy of needs and are considered an extension of the literature review. Besides, the findings can raise awareness for the government agencies, policymakers, and counsellors to develop strategies to reduce happiness materialism and increase SWB among Malaysian young adults.